2014
DOI: 10.1177/0731948714529772
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Responsiveness to Early Literacy Intervention

Abstract: The purpose of this review was to update previous reviews on factors related to students’ responsiveness to early literacy intervention. The 14 studies in this synthesis used experimental designs, provided small-group or one-on-one reading interventions, and analyzed factors related to responsiveness to those interventions. Participants were students who required intervention supports, with the majority identified as at-risk learners. Factors identified as consistently predictive included word identification, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
39
1
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(48 citation statements)
references
References 36 publications
5
39
1
3
Order By: Relevance
“…In a recent literature review of response to RTI, Lam and McMaster (in press) extended prior syntheses describing responsiveness to multi-tier interventions (e.g., Authors; Nelson, Benner & Gonzalez, 2003; Tran, Sanchez, Arellano,& Swanson, 2011) by reporting that students’ initial word identification, alphabetic principle, phonemic awareness, and fluency consistently predicted their responsiveness. Their findings appear to corroborate Vellutino et al's (2006) hypothesis that inadequate responders demonstrate a pattern along a continuum of severity on a variety of reading-related variables.…”
Section: Longitudinal Multi-tier Rti Researchmentioning
confidence: 96%
See 1 more Smart Citation
“…In a recent literature review of response to RTI, Lam and McMaster (in press) extended prior syntheses describing responsiveness to multi-tier interventions (e.g., Authors; Nelson, Benner & Gonzalez, 2003; Tran, Sanchez, Arellano,& Swanson, 2011) by reporting that students’ initial word identification, alphabetic principle, phonemic awareness, and fluency consistently predicted their responsiveness. Their findings appear to corroborate Vellutino et al's (2006) hypothesis that inadequate responders demonstrate a pattern along a continuum of severity on a variety of reading-related variables.…”
Section: Longitudinal Multi-tier Rti Researchmentioning
confidence: 96%
“…In the process, students with true cognitive-based reading disability could be identified. However, there is limited knowledge of the Tier 3 interventions for students with the most significant difficulties and disabilities; fewer still which have examined response to intervention longitudinally (Lam & McMaster, in press). Such knowledge could guide the next generation of RTI and special education research, particularly in terms of intervention design for students with persistent reading problems.…”
mentioning
confidence: 99%
“…Although SES is relatively easy to measure and known to be associated with reading skill, very few studies have asked whether participant response to an intervention varies in relation to SES. A review of 14 studies reported behavioral factors predicting responsiveness to literacy interventions (Lam and McMaster 2014).…”
Section: Introductionmentioning
confidence: 99%
“…One way to identify students in need of intensive intervention is to examine reading achievement prior to intervention. Research has noted that very low levels of initial reading achievement predict later low levels of reading achievement even when these students are provided less intensive Tier 2 type interventions (Al Otaiba & Fuchs, 2002; Lam & McMaster, 2014; Nelson, Benner, & Gonzalez, 2003; Vaughn & Linan-Thompson, 2003). Deficits in phonological awareness, rapid naming, fluency, and the alphabetic principle appear to be the most consistent predictors of initial response to intervention (Al Otaiba & Fuchs, 2002; Lam & McMaster, 2014; Nelson et al, 2003).…”
mentioning
confidence: 99%